Expert consensus for PVCR in severe, rigid and angular spinal deformity treatment: The Kunming consensus. (5th July 2017) - Xie, Jing-Ming; Chen, Zhong-Qiang; Shen, Jian-Xiong; Zhang, Xue-Song; Yang, Cao; Zheng, Zhao-Min; Qian, Bang-Ping; Tzeng, Shiau-Tzu; Tian, Hui-Zhong; Li, Chao; Wu, Ji; Wu, Zeng-Hui; et al.
In the past decades, an increasing number of surgeons started using posterior vertebral column resection (PVCR) to treat severe, rigid and angular spinal deformities. Little high-level evidence is available to guide surgical treatment. The aims of our study were to identify important surgical strategies and key technical points of Chinese experts who have extensive experience in the management of severe, rigid and angular spinal deformities using PVCR, and to standardize and unify the current core concepts. Workgroups of consensus were formed by selecting nationwide representing experts and comprehensive consultations. Eight task forces for major issues were established, then retrieval of literature, collection of expert opinions and writing of review articles were carried out. A modified Delphi process was chosen in round-table forum with three face-to-face meetings. Consensus was reached with items graded more than seven points including: indications and contraindications of PVCR; review PVCR in the evolution of spinal osteotomies; The corrective mechanism and safety of spinal cord; monitoring and responses of spinal cord crisis; characteristics and therapeutic outcome of pulmonary function; management of bleeding during PVCR; relationship of pedicle screw insertion and spinal cord safety; and analysis of non-neurologic complications and prevention strategies. In conclusion, The essential properties regarding PVCR procedure are tightly linked with various factors such as medical and surgical indication, range and level of vertebral column resection, strategies of correction, corrective efficiency and control of neurological risk. PVCR is used mainly for severe, rigid spinal deformity that is not manageable by other osteotomy techniques.